A Rare Complication of Chronic Otitis Media: Round Window Perforation - Dalgıç, Abdullah; Kandogan, Tolga (Fırat University, 2012)
Round window perforation is one of the rare complications of chronic otitis media. We reported a case who had bilateral tympanic membran perfora-tion with left sided round window fistula. Although it is very rare, it may seen round window perforation in the chronic otitis media. It is important to repair of round window perforation for preventing sensorineural hearing loss and inner ear infection.

Yuvarlak pencere perforasyonu kronik süpüratif otitis medianın nadir komplikasyonlarından biridir. Bileteral santral kuru perforasyonu olan ve operasyonu sırasında sol kulağındaki yuvarlak pencere perforasyonu tespit ettiğimiz bir olguyu sunduk. Kronik otitis mediada seyrek de olsa yuvarlak pencere perforasyonu olabilmektedir. Bu durumlarda yuvarlak pencere perforasyonun tamirinin yapılması hem total işitme kaybının önlenmesi hem de iç kulağın infeksiyonlardan korunması açısından oldukça önemlidir.
Kronik Otitis Media'nın Nadir Bir Komplikasyonu: Yuvarlak Pencere Perforasyonu